Studi Komparatif Sistem Hukum Wakaf Antara Negara Indonesia dan Singapura - Kadir, Fifi Musfira M. (Robust: Research of Business and Economics Studies, 2024)
Waqf is a legal act of wakif to separate and or surrender part of his property to be used forever or for a certain period of time according to his interests for the purposes of worship and/or general welfare according to sharia. Indonesia and Singapore, are 2 different countries where Indonesia is an Islamic country while Singapore is a secular country. This study analyzes the differences between the Indonesian and Singaporean state waqf legal systems. The benefit is in expanding the discourse on waqf law at the international level. The type of research is literature that uses a normative juridical approach, the type of data is secondary data consisting of primary, secondary and tertiary legal materials, the data analysis method is comparative study. The results of the study explain that the implementation of waqf law between Indonesia and Singapore has its own characteristics that are adapted to the typology of its people.